Interfacial transport properties between a strongly correlated transition metal oxide and a metal: Contact resistance in Fe3O4/M (M=Cu, Au, Pt) nanostructures - SHVETS, IGOR (My University, 2010)
Multiterminal measurements have typically been employed to examine electronic properties of strongly correlated electronic materials such as transition metal oxides without the influence of contact effects. In contrast, in this work we investigate the interface properties of Fe3O4 with different metals, with the contact effects providing a window on the physics at work in the correlated oxide. Contact resistances are determined by means of four-terminal electrical measurements as a function of source voltage and temperature. Contact resistances vary systematically with the work function of the electrode metal, phi(M), M=Cu, Au, and Pt, with higher work function yielding lower contact resistance. This trend and the observation that contact resistances are directly proportional to the Fe3O4 resistivity are consistent with modeling the oxide as an effective p-type semiconductor with hopping transport. The jumps in contact resistance values at the bias-driven insulator-metal transition have a similar trend with phi(M), consistent with the transition mechanism of charge gap closure by electric field.
PUBLISHED
Keywords: VERWEY; TRANSITION; MAGNETITE; MEMORY; DEVICES; FILMS; Nanoscience & Materials